Online emergency mapping based on disaster scenario and data integration. (2nd October 2021) - Ren, Fu; Li, Yiwen; Zheng, Zhihe; Yan, Han; Du, Qingyun
ABSTRACT: Emergency mapping is a task that requires abundant professional knowledge and complex operations, especially in high timeliness demands in disaster scenarios. The operation of the conventional cartographic system based on GIS in the desktop environment is complicated and requires operators to have strong professional skills, while the network environment provides low-cost, unified geographical data services and easy-to-use operation without using any specific software. In this paper, we propose an online emergency mapping framework, which is a novel idea for rapid mapping and combining multi-source heterogeneous disaster data with cartographer knowledge. Through a disaster scenario model for emergency mapping, the corresponding relationship between scenarios and map groups can be understood. Through disaster data integration, knowledge rules, mapping templates, map symbol engines, and a simple wizard, an emergency response map can be rapidly produced. With the support of the techniques mentioned above, a prototype system is developed to verify the efficiency and validity of the framework. The results demonstrate that a framework that can effectively assist decision makers in displaying the present situation clearly and accurately has high practical value. The study also provides a novel perspective for shortening the mapping cycle in emergencies.